The Implementation of the School Literacy Movement (GLS) Program to Foster Reading Interest Among Grade III Students at SD Negeri 38 Payakumbuh - Rahmi, Felly Lailatul; Oktira, Yona Syaida; Efrina, Gusnita; Efendi , Nofriza (The Future of Education Journal, 2025)
This research stems from students’ low reading interest. Objectives encompass illustrating the implementation of the School Literacy Movement program within learning activities to foster reading interest among third-grade students at SD Negeri 38 Payakumbuh and identifying factors supporting and hindering that program’s execution. Employing a qualitative case study approach, data collection methods include observation, interviews, and documentation. Data analysis unfolds across three stages: data reduction, data presentation, and drawing conclusions. Participants comprise third-grade homeroom teachers along with their students. Findings reveal implementation of the School Literacy Movement through several initiatives: 15‑minute daily reading before lessons kick off, a Love‑Reading Campaign, a reading corner, and class bulletin boards. Supporting factors include available facilities and infrastructure, presence of a reading corner, and classroom bulletin boards. Meanwhile, obstacles comprise limited reading materials, students’ low reading interest, and inadequate facilities.